2020
DOI: 10.1021/acsnano.0c01579
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Field of Explosive Trace Detection

Abstract: Explosive trace detection (ETD) technologies play a vital role in maintaining national security. ETD remains an active research area with many analytical techniques in operational use. This review details the latest advances in animal olfactory, ion mobility spectrometry (IMS), Raman and colorimetric detection methods. Developments in optical, biological, electrochemical, mass and thermal sensors are also covered in addition to the use of nanomaterials technology. Commercially available systems are presented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 345 publications
(564 reference statements)
0
70
0
Order By: Relevance
“…Explosives not only play a vital role in industrial processing and construction but also remain a threat to national security. Recently, many researchers have focused on the development of the analytical technologies for trace explosive detection of specific gases, which impact harmfully to humans or environmentally toxic 55 . Graphene‐based sensors were demonstrated that platforms were designed to incorporate pristine graphene, graphene oxide, and nanopatterned graphene, which showed excellent potential in the explosive trace detection 94 .…”
Section: Hazardous Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explosives not only play a vital role in industrial processing and construction but also remain a threat to national security. Recently, many researchers have focused on the development of the analytical technologies for trace explosive detection of specific gases, which impact harmfully to humans or environmentally toxic 55 . Graphene‐based sensors were demonstrated that platforms were designed to incorporate pristine graphene, graphene oxide, and nanopatterned graphene, which showed excellent potential in the explosive trace detection 94 .…”
Section: Hazardous Chemicalsmentioning
confidence: 99%
“…Applications of the nanomaterials‐based nanosensor platforms toward on‐site detection of hazardous materials in chemical accident. Reproduced with permission 55 …”
Section: Introductionmentioning
confidence: 99%
“…Kneipp reported SERS spectra from TNT on colloidal silver and gold particles for the first time in 1995 [ 19 ]. Since then, several commercially available SERS substrates as well as custom-made substrates have been used for the purpose of explosives detection [ 20 , 21 , 22 , 23 , 24 ]. Klarite substrates, composed of an array of inverted pyramidal-shaped pits etched into silicon, are the most well-characterized commercial substrate for SERS [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though very sensitive, serious problems with SERS signals are stability, reproducibility, and insufficient performance during practical applications, which may be due to the weak interaction between molecules and sensing substrates [ 24 , 33 , 34 ]. Recently, we have reported highly sensitive and uniform SERS substrates fabricated through simple processes of e-beam evaporation, rapid thermal annealing, and wet chemical etching [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the environmental andh umanitarian implications that are generated by the presence of landmines aroundt he world, the recentu psurge of terrorism has made the rapid, selective, and sensitived etection of explosives critical in border controla nd homelandsecurity. [19] Variationso f the luminescent properties of linear and porous organic polymers in the presenceo ft he analytes have been extensively used to detecte xplosive compounds such as electron-deficient nitroaromatics (NACs). [20][21][22][23][24] Comparatively,c oordination polymers have been much less investigated in this area.…”
Section: Introductionmentioning
confidence: 99%